Lived Experiences: Educators’ Perspectives in Assessment Within an Online Distance Education Nursing Programme - Simon-PeterKafui Aheto; Joseph Kwame Sasu; Valentina Arkorful (SAGE Open)
It is rare to run practical and Health Online and Distance Education professional programmes in West Africa. This research identifies one of the rare nursing programmes by an Online Distance Education mode. It further explored the lived experiences of a total of 13 top managers and educators (four females and nine males) who primarily organise, coordinate, and administer Distance Education programmes at the University of Ghana including the Nursing programme. Researchers reviewed aspects of Online Distance Education such as nature, assessment, benefits and challenges and quality assurance issues. Design Thinking was used as a theoretical unpinning to the epistemological lens of this qualitative case study. Results were thematically analysed under generated 12 themes. This study found that due to the nature of students; professional nurses, asynchronous systems were heavily employed and the university’s own coining of terms such as online offsite (off-campus) and online onsite (on-campus) to decipher the exact location of learners especially for mode of assessments whether off-campus or for on-campus. Reliance on Similarity software for plagiarism checking using Turnitin software assisted the educators. Researchers recommend for further research to cover at least two institutions that run similar Nursing programme in Ghana for results comparability purposes.